(untitled) (Research, Society and Development, 2020)
The study aims to analyze the scientific evidence on home birth and how the work of nurses is developing in their daily lives. It is an integrative review of the literature through research in the Virtual Health Library (VHL) with pre-selected descriptors, obtaining studies indexed in the LILACS, MEDLINE and BDENF databases from 1998 to the first half of 2017. Twelve articles were found, divided by similarity and used as a basis for the creation of 3 categories for discussion: I Historical and Cultural Restitution of Home Delivery: transition to institutionalized delivery, with 3 articles; II Performance of Obstetric Nurses in Home Delivery, with 5 articles; and III The choice for home delivery and the role of the nurse in strengthening it, with 4 articles. The detailed reading of the articles allowed us to observe that home birth has been approached as a channel of trust by the woman with herself and with the professional, since both become responsible for making decisions regarding the planning of their care, so that the woman participates actively and is the protagonist of their delivery. The study aims to analyze the scientific evidence on home birth and how the work of nurses is developing in their daily lives. It is an integrative review of the literature through research in the Virtual Health Library (VHL) with pre-selected descriptors, obtaining studies indexed in the LILACS, MEDLINE and BDENF databases from 1998 to the first half of 2017. Twelve articles were found, divided by similarity and used as a basis for the creation of 3 categories for discussion: I Historical and Cultural Restitution of Home Delivery: transition to institutionalized delivery, with 3 articles; II Performance of Obstetric Nurses in Home Delivery, with 5 articles; and III The choice for home delivery and the role of the nurse in strengthening it, with 4 articles. The detailed reading of the articles allowed us to observe that home birth has been approached as a channel of trust by the woman with herself and with the professional, since both become responsible for making decisions regarding the planning of their care, so that the woman participates actively and is the protagonist of their delivery.